“The compass of possibilities”: Re-Mapping the Suburbs of Los Angeles in the Writings of D.J. Waldie - Neil Campbell (European Journal of American Studies)
This article uses the works of the writer, memoirist, and Lakewood, California public official, D. J. Waldie to deepen our concept of “region” and to re-assess many of the stereotypical discourses associated with the American suburbs. In the fashionable parlance of Mike Davis’ City of Quartz, Los Angeles has become defined by its “suburban badlands”; however, Waldie‘s work takes a different view in which his suburban home in LA is the focus for a more complex, multi-faceted approach to post-war suburbia. Typified by his re-assessment of the suburban grid as a “compass of possibilities,” his writings encourage a more nuanced and layered view of the communities and cultures fostered in such places. His key work Holy Land is an argument about why a disregarded place, an ordinary place like suburbia, can in fact contain qualities of life that are profound and reassuring. Through examining his work in its cultural and theoretical context this article looks below the expected “grid” of suburbia to demonstrate the rich life beyond its apparent anonymity.